Assessing the Potential for Sustainable Aquaculture Development in Cambodia - Joffre, Olivier M.; Freed, Sarah; Bernhardt, James; Teoh, Shwu Jiau; Sambath, Sak; Belton, Ben (Frontiers in Sustainable Food Systems, 2021)
Inland capture fisheries make a larger contribution to livelihoods and food security in Cambodia than perhaps any other country, but are under threat from growing anthropogenic pressures. Policy discourse in Cambodia increasingly frames aquaculture as a viable alternative to capture fisheries, and seeks to promote its development. This paper presents results from the first comprehensive survey of Cambodia’s aquaculture value chain. The study combines qualitative (46 Key Informant Interviews) and quantitative surveys (1,204 farmers and 191 other aquaculture value chain actors) to investigate potential for aquaculture in Cambodia to grow, support livelihoods, and contribute to food security. We found the following: (i) The fish farm sector in Cambodia is comprised mainly of small family farms raising carnivorous fish species or pangasius, using direct inputs of “trash fish” harvested from the wild; (ii) Most fish seed and pelleted feed are imported, and domestic producers of these inputs struggle to compete; (iii) Fish farmed in Cambodia is mostly sold live. Farm fish are more expensive than the main species harvested from inland capture fisheries, and struggle to compete with imported farmed fish; (iv) Capture fisheries employ many times more people than aquaculture; (v) Space for aquaculture is limited because few locations have both perennial access to water and protection from flooding. These findings raise questions about the potential of Cambodia’s aquaculture sector, as currently organized, to contribute significantly to employment, food and nutrition security, and rural economic development. We propose actions to improve the sector’s sustainability and contribute to desirable development outcomes.